2010
DOI: 10.2337/db10-0190
|View full text |Cite
|
Sign up to set email alerts
|

MafA and MafB Regulate Genes Critical to β-Cells in a Unique Temporal Manner

Abstract: OBJECTIVESeveral transcription factors are essential to pancreatic islet β-cell development, proliferation, and activity, including MafA and MafB. However, MafA and MafB are distinct from others in regard to temporal and islet cell expression pattern, with β-cells affected by MafB only during development and exclusively by MafA in the adult. Our aim was to define the functional relationship between these closely related activators to the β-cell.RESEARCH DESIGN AND METHODSThe distribution of MafA and MafB in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
288
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(314 citation statements)
references
References 50 publications
17
288
2
1
Order By: Relevance
“…In the perinatal period, a transition from Mafb to Mafa accompanies differentiation of beta cells in a temporal way, where Mafb expression is gradually reduced as Mafa expression increases so that mature beta cells only express Mafa [10,16]. Interestingly, a recent study showed that Mafb was re-expressed in proliferative beta cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the perinatal period, a transition from Mafb to Mafa accompanies differentiation of beta cells in a temporal way, where Mafb expression is gradually reduced as Mafa expression increases so that mature beta cells only express Mafa [10,16]. Interestingly, a recent study showed that Mafb was re-expressed in proliferative beta cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…Diet-induced changes in the temporal expression of transcription factors important for beta cell differentiation and maturation, such as v-maf musculoaponeurotic fibrosarcoma oncogene (MAF) homologue A and B and pancreatic duodenal homeobox-1 (PDX1), very likely play a role in development of the phenotype of LP offspring [14][15][16]. The regulation of these factors is, however, not fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MafB is essentially absent from mature adult b-cells and its expression is restricted to a-cells in the adult pancreas. The switch from MafB þ to MafA þ in b-cells occurs during a period of b-cell maturation and this process is associated with up-regulation of Pdx1 expression (Nishimura et al 2006;Artner et al, 2010). MafA mutants have no effect on endocrine cell development but the mice become glucose-intolerant postnatally .…”
Section: Class Iii: Maturation Factorsmentioning
confidence: 99%
“…Whereas MafA function is b-cell specific, MafB is required for both a-cell and b-cell differentiation/ maturation, and is a more potent regulator of embryonic b-cell development than MafA. MafB À/À mice have reduced a and b-cell numbers, as well as some form of apparently delayed bcell development (Artner et al, , 2010.…”
Section: Class Iii: Maturation Factorsmentioning
confidence: 99%
“…Ucn3 is a late maturation marker for primary and stem cell-derived beta cells (Blum et al, 2012;van der Meulen et al, 2012) that continued to increase progressively weeks after beta cell expression of Nkx6-1 and Mafa reached steady state, and coincided with the gradual loss of Mafb from beta cells ( Figure 1A) (Artner et al, 2010).…”
Section: Ucn3-negative Immature Beta Cells Persist Throughout Lifementioning
confidence: 99%